2021
DOI: 10.1186/s12920-021-00885-3
|View full text |Cite
|
Sign up to set email alerts
|

A novel prognostic prediction model based on seven immune-related RNAs for predicting overall survival of patients in early cervical squamous cell carcinoma

Abstract: Background In this study, we aimed to mine immune-related RNAs expressed in early cervical squamous cell carcinoma to construct prognostic prediction models. Methods The RNA sequencing data of 309 cervical squamous cell carcinoma (CSCC) cases, including data of individuals with available clinical information, were obtained from The Cancer Genome Atlas (TCGA) database. We included 181 early-stage CSCC tumor samples with clinical survival and prognos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 39 publications
1
5
0
Order By: Relevance
“…Interestingly, in a previous analysis, we showed that the high expression of VCAM1 indicates a good prognosis in cervical cancer patients, which is in line with the results of a previous study ( 39 ). To examine the aberrant expression of VCAM1 in cervical tumor tissues and further explore the relationship between miR-95-3p and VCAM1 , we collected clinical cervical tumor tissue samples and downregulated the expression of miR-95-3p with an inhibitor in the HeLa cells.…”
Section: Resultssupporting
confidence: 92%
“…Interestingly, in a previous analysis, we showed that the high expression of VCAM1 indicates a good prognosis in cervical cancer patients, which is in line with the results of a previous study ( 39 ). To examine the aberrant expression of VCAM1 in cervical tumor tissues and further explore the relationship between miR-95-3p and VCAM1 , we collected clinical cervical tumor tissue samples and downregulated the expression of miR-95-3p with an inhibitor in the HeLa cells.…”
Section: Resultssupporting
confidence: 92%
“…Recent years the net reclassification index (NRI), integrated discrimination improvement (IDI) have become the two popularity alternatives assessment in risk evaluation or prediction between different models (21,22). We searched ten recently published CESC prognostic signatures, and used NRI, IDI method in "survIDINRI" package to compare the clinical benefits of our signature and published signatures (23)(24)(25)(26)(27)(28)(29)(30)(31)(32).…”
Section: Clinical Benefits Evaluation Of Cesc Os Signaturesmentioning
confidence: 99%
“…In another study, an autophagy-related gene prognostic risk model was applied to provide a reference for CC patients to make precise treatment strategy, and the AUCs for prognostic accuracy reached 0.772 for the training set and 0.889 for the verification set. Other gene sets for establishing prognostic model in CC included immune-related genes [ 15 ], DNA methylation [ 16 ], and lymph node metastasis [ 17 ].…”
Section: Discussionmentioning
confidence: 99%